Global gene expression analysis of human erythroid progenitors. - Merryweather-Clarke, A; Atzberger, A; Soneji, S; Gray, N; Clark, K; Waugh, C; McGowan, S; Taylor, S; Nandi, A; Wood, W; Roberts, D; Higgs, D; et al. (2011)
Understanding the pattern of gene expression during erythropoiesis is crucial for a synthesis of erythroid developmental biology. Here, we isolated 4 distinct populations at successive erythropoietin-dependent stages of erythropoiesis, including the terminal, pyknotic stage. The transcriptome was determined using Affymetrix arrays. First, we demonstrated the importance of using defined cell populations to identify lineage and temporally specific patterns of gene expression. Cells sorted by surface expression profile not only express significantly fewer genes than unsorted cells but also demonstrate significantly greater differences in the expression levels of particular genes between stages than unsorted cells. Second, using standard software, we identified more than 1000 transcripts not previously observed to be differentially expressed during erythroid maturation, 13 of which are highly significantly terminally regulated, including RFXAP and SMARCA4. Third, using matched filtering, we identified 12 transcripts not previously reported to be continuously up-regulated in maturing human primary erythroblasts. Finally, using transcription factor binding site analysis, we identified potential transcription factors that may regulate gene expression during terminal erythropoiesis. Our stringent lists of differentially regulated and continuously expressed transcripts containing many genes with undiscovered functions in erythroblasts are a resource for future functional studies of erythropoiesis. Our Human Erythroid Maturation database is available at https://cellline.molbiol.ox.ac.uk/eryth/index.html. [corrected].